Sistemas capacitivos aplicados na avaliação da umidade relativa de madeira de pinus - Ferreira, Jéssimon (2017)
This work proposes to characterize a sensor able to identify the Pinus wood moisture status of the Elliotti species. The designed sensor was implemented by two metal plates of rectangular geometric shape forming a bipolar capacitive component. To conditionate the sensor signals, a bridged electric circuit has been implemented and the capacitive sensor integrated into this electrical circuit to be fed by a high frequency alternating current power source (VCA). The purpose of this integration is to obtain in the bridge’s branches an electric signal variation, as a capacitive reactance variation function between the sensor plates. Capacitive reactance is an electrical property identified in the wood when it acts as a dielectric between the sensor metal plates, and may suffer variations depending on the sample humidity variation. With the Pinus wood electric reactance variation, it was possible to record the humidity variation of the samples having as a parameter the electric signals variations provided by the bridge as a capacitive reactance function. In order to obtain the records and perform a comparison method between the humidity of the samples tests and the electrical signal, the samples were initially saturated with water and during a drying process, and the values of the electrical quantities involved were collected during equal time periods, until reaching the dry mass weight. The differential of this work in relation to others of the same theme, is its ability to identify in only one action, without destructive processes usage, small humid spots within a larger area of the analyzed material. The obtained results can be visualized through tables, tables and graphs.